Growth in Children With Noonan Syndrome and Effects of Growth Hormone Treatment on Adult Height - Libraro, Annachiara; D’Ascanio, Vito; Cappa, Marco; Chiarito, Mariangela; Digilio, Maria Cristina; Einaudi, Silvia; Grandone, Anna; Maghnie, Mohamad; Mazzanti, Laura; Mussa, Alessandro; Patti, Giuseppa; Scarano, Emanuela; et al. (Frontiers in Endocrinology, 2021)
Objectives. Growth impairment is a common manifestation in Noonan syndrome (NS). Recombinant human GH (rhGH) treatment has been shown to increase growth and adult height (AH) in a few studies. We aimed to evaluate the growth trajectory towards the AH, and the effects of rhGH treatment in a large cohort of NS children. Methods. Retrospective, multicenter, cohort study including subjects with genetic diagnosis of NS. A total of 228 NS patients, 154 with PTPN11 mutations, 94 who reached AH, were recruited. Auxological data were collected at 2, 5, and 10 years, at pubertal onset, at AH. Sixty-eight NS subjects affected with GH deficiency (GHD) were treated with rhGH at mean dose of 0.24 mg/kg per week until AH achievement. Results. ANOVA analysis showed a significant difference between birth length and height standard deviation scores (HSDS) at the different key ages (p<0.001), while no significant differences were found between HSDS measurements at 2, 5, and 10 years, at pubertal onset and at AH. HSDS increased from -3.10 ± 0.84 to -2.31 ± 0.99 during rhGH treatment, with a total height gain of 0.79 ± 0.74, and no significant difference between untreated and treated NS at AH. Conclusions. rhGH treatment at the standard dose used for children with GH idiopathic deficiency is effective in improving growth and AH in NS with GHD. Further studies are needed to assess genotype-specific response to rhGH treatment in the different pathogenic variants of PTPN11 gene and in the less common genotypes.